Medicinal Plants in the Treatment of Peptic Ulcer Disease: A Review - Ardalani, Hamidreza; Hadipanah, Amin; Sahebkar, Amirhossein (Mini Reviews in Medicinal Chemistry, 2020)
Peptic Ulcer Disease (PUD) is the most common disorder of the stomach and duodenum, which is associated with Helicobacter pylori infection. PUD occurs due to an imbalance between offensive and defensive factors and Proton Pump Inhibitors (PPI), Nonsteroidal Anti-Inflammatory Drugs (NSAIDs) and antibiotics are frequently used for the treatment. Recently, medicinal plants have emerged as efficacious, safe and widely available alternative therapies for PUD. The aim of this review was to study the medicinal plants and phytochemicals, which have been used for PUD treatment to evaluate the potential role of natural compounds to develop herbal remedies for PUD. Information was obtained using a literature search of electronic databases, such as Web of Science, Google Scholar, PubMed, Sci Finder, Reaxys and Cochrane. Common and scientific names of the plants and keywords such as ‘peptic ulcer’, ‘gastric ulcer’, ‘stomach ulcer’ and ‘duodenal ulcer’ were used for search. Eventually, 279 plants from 89 families were identified and information on the plant families, part of the plant used, chemical constituents, extracts, ulcer model used and dosage were abstracted. The results indicated that most of the anti-PUD plants were from Asteraceae (7.1%) and Fabaceae (6.8%) families while flavonoids (49%), tannins (13%), saponins (10%) and alkaloids (9%) were the most common natural compounds in plants with anti-PUD activity.
Keywords: antioxidant